Applications of accelerator MS in pediatric drug evaluation. (August 2012) - Vuong, LT; Blood, AB; Vogel, JS; Anderson, ME; Goldstein, B
Accelerator MS (AMS) provides a novel method for obtaining and analyzing pharmacokinetics and pharmacodynamics in children. This paper reviews the scientific and ethical rationale for AMS in pediatric trials, the regulatory framework and general considerations with some specific examples of pediatric clinical trials using AMS. Microdosing in the context of this article refers to studies using a negligible amount (nanocuries) of 14 C as tracer, and AMS as a quantitative technique. The technology is by no means a panacea for the deficiency in pediatric clinical research; however, it lessens the challenges and provides the most quantitative tool for pediatric pharmacology studies.